Pengaruh Model Pembelajaran Jigsaw Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Otomatisasi Tata Kelola Kepegawaian Kelas XI OTKP di SMKN 1 Surabaya - Cynthia Lauren; Durinta Puspasari (Universitas Negeri Surabaya, 2020)
AbstractThis study aims to determine the influence of Jigsaw learning to students learning outcomes on the subjects of the governance Automation class XI OTKP at SMKN 1 Surabaya. This type of research is experimental research by using the research design of quasi experimental design with nonequivalent control group design. This study was conducted on students of XI OTKP 1 class as an experimental class and a grade XI class students. This research instrument uses a double-choice test to measure students cognitive abilities. Then, the data obtained analyzed test-t with independent test sample test, test-t, and score gain. The results showed that the Jigsaw learning model had a significant effect on student learning outcomes that could be demonstrated by the acquisition of test-t results with a level of significance 0,000 < 0.05. So it can be concluded that the learning model of Jigsaw has an influence on the outcome of learning outcomes of XI OTKP class in SMKN 1 Surabaya. The experiment class also has higher learning outcomes than the proven control class with an experimental class average value of 82.83 and a control class of 75.06.Keywords: jigsaw learning model; learning outcomes.